Aberrant glycosylation in schizophrenia: insights into pathophysiological mechanisms and therapeutic potentials - Feng, Yanchen; Sun, Lu; Dang, Xue; Liu, Diyan; Liao, Ziyun; Yao, Jianping; Zhang, Yunke; Deng, Ziqi; Li, Jinyao; Zhao, Min; Liu, Feixiang (Frontiers in Pharmacology, 2024)
Schizophrenia (SCZ) is a severe neuropsychiatric disorder characterized by cognitive, affective, and social dysfunction, resulting in hallucinations, delusions, emotional blunting, and disordered thinking. In recent years, proteomics has been increasingly influential in SCZ research. Glycosylation, a key post-translational modification, can alter neuronal stability and normal signaling in the nervous system by affecting protein folding, stability, and cellular signaling. Recent research evidence suggests that abnormal glycosylation patterns exist in different brain regions in autopsy samples from SCZ patients, and that there are significant differences in various glycosylation modification types and glycosylation modifying enzymes. Therefore, this review explores the mechanisms of aberrant modifications of N-glycosylation, O-glycosylation, glycosyltransferases, and polysialic acid in the brains of SCZ patients, emphasizing their roles in neurotransmitter receptor function, synaptic plasticity, and neural adhesion. Additionally, the effects of antipsychotic drugs on glycosylation processes and the potential for glycosylation-targeted therapies are discussed. By integrating these findings, this review aims to provide a comprehensive perspective to further understand the role of aberrant glycosylation modifications in the pathophysiology of SCZ.